Risk of Kidney Stones: Influence of Dietary Factors, Dietary Patterns, and Vegetarian–Vegan Diets - Pietro Manuel Ferraro (Nutrients, 2020)
Nephrolithiasis is a common medical condition influenced by multiple environmental factors, including diet. Since nutritional habits play a relevant role in the genesis and recurrence of kidney stones disease, dietary manipulation has become a fundamental tool for the medical management of nephrolithiasis. Dietary advice aims to reduce the majority of lithogenic risk factors, reducing the supersaturation of urine, mainly for calcium oxalate, calcium phosphate, and uric acid. For this purpose, current guidelines recommend increasing fluid intake, maintaining a balanced calcium intake, reducing dietary intake of sodium and animal proteins, and increasing intake of fruits and fibers. In this review, we analyzed the effects of each dietary factor on nephrolithiasis incidence and recurrence rate. Available scientific evidence agrees on the harmful effects of high meat/animal protein intake and low calcium diets, whereas high content of fruits and vegetables associated with a balanced intake of low-fat dairy products carries the lowest risk for incident kidney stones. Furthermore, a balanced vegetarian diet with dairy products seems to be the most protective diet for kidney stone patients. Since no study prospectively examined the effects of vegan diets on nephrolithiasis risk factors, more scientific work should be made to define the best diet for different kidney stone phenotypes.